Consumers Attitudes on Services of General Interest in the EU: Accessibility, Price and Quality 2000-2004 - Carlo Fiorio; M. Florio; S. Salini; P. Ferrari (Fondazione Eni Enrico Mattei (FEEM), 2007)
The research question addressed by this paper is a simple one: are European consumers happy with the services provided by the utilities after two decades of reforms? We focus on electricity, gas, water, telephone in the EU 15 Member States. The variables we analyse are consumers satisfaction with accessibility, price and quality, as reported in three waves of Eurobarometer survey, 2000-2002-2004, comprising around 47,000 observations. We use ordered logit models to analyze the impact of privatization and regulatory reforms, as represented by an OECD dataset, controlling for individual and country characteristics. Our results do not support a clear association between consumers satisfaction and a standard reform package of privatization, vertical disintegration, liberalization.
Keywords: L94; L95; L96; L50; 330; Consumers Satisfaction; Gas; Electricity; Telephone; Water; Eurobarometer; Konsumentenverhalten; Versorgungswirtschaft; EU-Staaten